Evaluasi English For Tourism Sebagai Sarana Komunikasi di Tempat Wisata Rohani (Bukit Doa Mahawu Tomohon Manado) - Verawaty, Hotliong; Tangkulung, Fadly; Tuwo, Tiara (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2024)
This study evaluates the usage of English for Tourism (ESP) as a means of communication at Bukit Doa Mahawu in Tomohon, Manado, Indonesia. English plays a crucial role as a global communication tool, especially in tourist destinations visited by international tourists. This research uses direct observation, interviews with stakeholders, and qualitative descriptive analysis to collect data. The research results show that the use of ESP at Bukit Doa Mahawu is very significant in facilitating communication. Out of 20 respondents, consisting of 5 managers and 15 visitors, 100% agree that ESP is important in providing clear information and descriptions of tourism facilities and attractions, presented in bilingual form (Indonesian and English). The research also found that tourist attractions, public facilities, and accessibility at Bukit Doa Mahawu are generally well-rated by the respondents. However, accessibility remains a challenge, especially for foreign tourists who do not use private vehicles. English for Tourism (ESP) plays a crucial role in enhancing the tourism experience at Bukit Doa Mahawu Tomohon by providing effective and inclusive communication for international visitors. This research suggests the improvement of English language skills for managers and the addition of bilingual directional signs and information to further maximize the tourism potential in the area.